Réponses

  • Omnes
  • Modérateur confirmé
2014-02-16T23:41:41+01:00
Salut,

x² + 13 = 48
x² = 48 - 13
x² = 35
x² - 35 = 0
(x+ \sqrt{35} )(x- \sqrt{35} ) = 0
x -  \sqrt{35} = 0
x =  \sqrt{35}
x +  \sqrt{35} = 0
x = - \sqrt{35}

7x² - 11 = 3x² + 13
7x² -3x² = 13 +11
4x² = 24
4x² - 24 = 0
(2x -  \sqrt{24} )(2x+ \sqrt{24} ) = 0
2x -  \sqrt{24} = 0
2x =  \sqrt{24}
x =  \sqrt{6}
2x+ \sqrt{24} = 0
2x = - \sqrt{24}
x = - \sqrt{6}

(5x-2)² = 36
(5x-2)² - 36 = 0
(5x-2+6)(5x-2-6) = 0
(5x +4)(5x-8) = 0
5x + 4 = 0
5x = -4
x = -4/5

5x - 8 = 0
5x = 8
x = 8/5

(3x+2)² = (5x-4)²
(3x+2)² - (5x-4)² = 0
[(3x + 2) - (5x-4)][(3x+2)+(5x-4)] = 0
(3x+2-5x+4)(3x+2+5x-4) = 0
(8x + 6)(8x -2) = 0
2(4x+3)(8x-2) = 0
4(4x+3)(4x-1) = 0
4x + 3 = 0
4x = -3
x = -3/4
4x - 1 = 0
4x = 1
x = 1/4

Bonne soirée !